Respuesta :

Answer:

Step-by-step explanation:

t=(-2.74 + sqrt(2.74^(2)-4*-4.9*(-10))) / -2*-4.9

t=(-2.74 + sqrt(7.5076-4*+49))/9.8

t=(-2.74 + sqrt(7.5076+45))/9.8

t=(-2.74 + sqrt(52.5076))/9.8

t=(-2.74/9.8)+(sqrt(52.5076))/9.8

this is simplest form, next will be rounded answers

t=0.45981763305

Answer:

no real solutions

see below

Step-by-step explanation:

It looks like a quadratic formula

t= -2.74 + sqrt(2.74^(2)-4*-4.9*(-10)) -: 2*-4.9

[tex]t = \frac{-2.74 +\sqrt{2.74^2 - 4*(-4.9)*(-10)} }{2*(-4.9)}[/tex]

[tex]t = \frac{-2.74 + \sqrt{7.5076 -196} }{-9.8} = \frac{-2.74 + \sqrt{-188.4924} }{-9.8}[/tex]

[tex]t = \frac{-2.74 + 13.73i}{-9.8 }[/tex]

i = [tex]\sqrt{-1}[/tex]

Otras preguntas